2020
DOI: 10.2217/epi-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis to Identify Driving Factors in Colorectal Cancer

Abstract: Aim: We aim to identify driving genes of colorectal cancer (CRC) through multi-omics analysis. Materials & methods: We downloaded multi-omics data of CRC from The Cancer Genome Atlas dataset. Integrative analysis of single-nucleotide variants, copy number variations, DNA methylation and differentially expressed genes identified candidate genes that carry CRC risk. Kernal genes were extracted from the weighted gene co-expression network analysis. A competing endogenous RNA network composed of CRC-related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…(40) A study by Xu et al identi ed that REP15 could serve as a novel prognostic gene for CRC and low expression of REP15 was associated with unfavorable prognosis of CRC, besides, they also found that the high expression of REP15 was positively correlated with the p53 pathway, and negatively correlated with glycerophospholipid metabolism, hedgehog and insulin pathways. (41) The gene B3GNT6 encodes a glycosyltransferase, which is capable of adding progressive carbohydrates to form a core 3 O-glycan structure and only appears in speci c tissues, such as the colon. It has been reported that the core 3 structure in colon cancer tissue decreases with the decrease of core 3 synthase activity.…”
Section: Discussionmentioning
confidence: 99%
“…(40) A study by Xu et al identi ed that REP15 could serve as a novel prognostic gene for CRC and low expression of REP15 was associated with unfavorable prognosis of CRC, besides, they also found that the high expression of REP15 was positively correlated with the p53 pathway, and negatively correlated with glycerophospholipid metabolism, hedgehog and insulin pathways. (41) The gene B3GNT6 encodes a glycosyltransferase, which is capable of adding progressive carbohydrates to form a core 3 O-glycan structure and only appears in speci c tissues, such as the colon. It has been reported that the core 3 structure in colon cancer tissue decreases with the decrease of core 3 synthase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to study CRC heterogeneity, our current knowledge in this field is just the tip of the iceberg. Expanding next-generation sequencing (NGS), single-cell sequencing, and whole-exome sequencing techniques along with the application of omics data at various levels, including genomics, epigenomics, transcriptomics, peptidomics, proteinomics, and metabolomics, could give us valuable information on the heterogeneity of CRCs (116)(117)(118)(119)(120)(121)(122)(123).…”
Section: Heterogeneity Assessment Methodsmentioning
confidence: 99%
“…Apart from bMERB family members, Rep15 is another Rab15 effector molecule that regulates transferrin receptor trafficking. Recently multi-omics analysis data suggested REP15 as a novel colorectal cancer-specific driving gene 17 . Rep15 interacts with Rab15 at the ERC, and overexpression and depletion of Rep15 by si RNA attenuates the recycling of internalized transferrin receptor recycling via ERC without affecting receptor trafficking through sorting endosomes 18 .…”
Section: Introductionmentioning
confidence: 99%